Review of Vid Simoniti, Artists Remake the World: A Contemporary Manifesto (2023), New Haven: Yale University Press - Sue Spaid (Aesthetic Investigations)
With Artists Remake the World: A Contemporary Manifesto (2023), Vid Simoniti surveys recent exhibition-based contemporary art (most since 2016) that ‘glimpse possibilities for repairing the world’. By deferring to institutional definitions of art, Simoniti avoids having to defend whether exhibited objects are art, yet this approach ignores the fact that not all exhibited objects begin/endure as art, let alone begin/endure as political art. Early on, he admits of a paradox regarding exhibition-based political art, that is, it can feel ‘forbiddingly abstruse, experimental, hard to access, inward looking, even elitist’.